Bioinformatics analysis of gene expression microarray in lupus nephritis - JIANG Qiu-zhu; YANG Hui; ZHOU Xiao-shuang (Linchuang shenzangbing zazhi)
Objective To explore the potential pathogenesis of lupus nephritis(LN)with bioinformatics method.Methods The gene expression profiles of normal kidney tissue and LN kidney tissue were obtained by GEO database.The gene expression in the two kinds of tissues was analyzed look for differential genes.Enrichment analysis of the differential genes in the progression of LN were performed by DAVID database,and the differential genes were visualized analytically by STRING database and Cytoscape.Results 146 up-regulated genes and 28 down-regulated genes were screened out.In terms of cellular pathway,differential genes are mainly involved in type I interferon signaling pathway;in cell localization,differential genes are mainly distributed in extracellular bodies;in molecular function,differential genes are mainly related to MHC class II receptor activity.KEGG analysis showed that the differential genes were associated with the signaling pathways for influenza A virus infection,Staphylococcus aureus infection,herpes simplex virus infection,leishmaniasis and asthma.By screening it was found that IFI35,MX2,OAS3,IFI6,IRF7,OAS2,IFIT2,RSAD2,OAS1,MX1 are the core genes in the interaction network of proteins related to LN risk.Conclusions Through the analysis of the data set,the key genes in the progression of LN were found by using bioinformatics method,which provided the basis for finding some valuable LN markers.